Understanding sex - Lemire, Maureen; Ward, Jonathan; Bergen, Candice; Discovery Channel (Firm).; Discovery Communications, Inc. ([S.l.] Discovery Communications, 1994)
This program discusses the science of sex and how researchers find more evidence that reproduction choreographs the dance of life.
Written by Maureen Lemire and Jonathan Ward ; Senior producer: Susan Winslow ; Executive producer, Discovery Networks: Nancy LeBrun ; Associate producer: Moria Ratchford ; For Discovery Networks, associate producer: Anne Hubbel Lustig ; Series producer: Jonathan Ward.
Narrated by Candice Bergen.
VCD.
Keywords: Sex (Biology).; Hormones, Sex; Human reproduction